2018
DOI: 10.1007/s11064-017-2460-0
|View full text |Cite
|
Sign up to set email alerts
|

Methionine in Proteins: It’s Not Just for Protein Initiation Anymore

Abstract: Methionine in proteins is often thought to be a generic hydrophobic residue, functionally replaceable with another hydrophobic residue such as valine or leucine. This is not the case, and the reason is that methionine contains sulfur that confers special properties on methionine. The sulfur can be oxidized, converting methionine to methionine sulfoxide, and ubiquitous methionine sulfoxide reductases can reduce the sulfoxide back to methionine. This redox cycle enables methionine residues to provide a catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 116 publications
(125 reference statements)
1
80
0
3
Order By: Relevance
“…Hence, in the remainder we will present only a few examples that together outline the evolutionary potential of methionine sulfoxidation as a regulatory strategy. A more extensive review can be found at Reference .…”
Section: Methionine Sulfoxidation Mediates the Regulation Of Diverse mentioning
confidence: 99%
“…Hence, in the remainder we will present only a few examples that together outline the evolutionary potential of methionine sulfoxidation as a regulatory strategy. A more extensive review can be found at Reference .…”
Section: Methionine Sulfoxidation Mediates the Regulation Of Diverse mentioning
confidence: 99%
“…It is tempting to speculate that the Met clustering could play a particular role for the regulation of ligand access in THB11, especially in the context of an algal host that photosynthetically produces reactive oxygen species on a regular basis. Met residues are prone to oxidation, a process that is reversible by methionine sulfoxide reductases and employed for antioxidative defense as well as for protein activity regulation [81]. We do not know where the THB11 C terminus would be located and if it would shield the ST access site, respectively.…”
Section: Figmentioning
confidence: 98%
“…Авторы работ [1,2] окислении может быть обусловлена окислением остатка метионина, АαMet476, нарушающего способность αC-областей окисленных молекул участвовать в латеральной агрегации протофибрилл. В этой связи следует отметить, что предпочтительное окисление АαMet476 по сравнению с другими многочисленными остатками метионинов в Аα-цепи свидетельствует о том, что этот остаток, по всей видимости, локализован на поверхности белка и может окисляться без существенных потерь в функциональной активности белка [15]. Кроме того, выявленные окислительные модификации других остатков, локализованных на αС-доменах и αC-коннекторах, также, вероятно, могут способствовать ослаблению взаимодействия αC-αC.…”
Section: биохимия биофизика молекулярная биологияunclassified